Comparison of the Principles of Scientific Management and Lean Manufacturing (Journal of Universal Excellence, 2026)
Research Question (RQ): Do the principles and factors of lean manufacturing bring fundamentally different principles from Taylor’s scientific management?Purpose: We want to check whether the principles and factors of lean manufacturing are dramatically different compared to scientific management.Method: We used an integrative review of the professional literature for the past 40 years (1980–2020) in which the principles and factors of scientific management and lean manufacturing were described.Results: The authors of the studied scientific publications defend the opinion that the principles and factors of lean production do not bring significantly different principles from Taylor's scientific management. For this, his works need to be read and interpreted through the glasses of socio-economic and social differences at the time of the creation of his works (early twentieth century) and today.Organization: Often the reason for introducing changes in the organization is wrong, instead of new organizational receipts, the company only needs to strictly adhere to existing principles combined with the commitment of management. Awareness that no organizational reception will help an organization without committed leadership and that anyone with committed leadership will help it saves organizations a lot of time and money..Society: Progress and success in the organization can be achieved equally by applying the principles of scientific management as by the principles of lean organization and without the advice of external consultants, the condition for this is the consistent application of the principles of one or the other approach. In this way, we achieve that as many organizations as possible are committed to the actual implementation of these principles in their processes, regardless of the concept from which they come..Originality: Success in an organization can be achieved by applying the principles of scientific management on an equal footing with the principles of lean organization and without the advice of external consultants. The most important thing for this is the commitment and commitment of top management to the implemented principles.Limitations/Future Research: A survey on our findings among Slovenian management would sensibly complement our article.
Keywords: manager; principles; modern receipts; Taylor; performance; lean manufacturing; scientific management